Interventions to Reduce Anxiety in Burn Patients: A Scoping Review - Yadi, Deni Alia; Pahria, Tuti; Purba, Chandra Isabella Hostanida (Indonesian Journal of Global Health Research, 2024)
Anxiety in burn patients is a serious problem that can worsen the patient's condition and slow the healing process. Effective management of anxiety can improve the patient's quality of life and support their recovery. Although various non-pharmacological interventions have been proposed, there is still uncertainty regarding the effectiveness and application of each technique in the context of burn care. Objective: To explore various non-pharmacological interventions used to reduce anxiety in burn patients. The method used is scoping review. Articles were selected from four major databases: CINAHL, PubMed, and Scopus, using keywords namely “burn patients”, “anxiety”, “intervention”, and “burn injury”. Inclusion criteria included studies involving adult patients with burns, original research with RCT or quasi-experimental design, using experimental or quasi-experimental design, and articles published in the last 10 years (2014-2023). Data were extracted using manual tables and analyzed descriptively qualitatively. Based on initial research, we found 453 articles. After selected by authors, Nine articles met the inclusion criteria. The interventions discussed included aromatherapy, Benson relaxation technique, music therapy, Swedish and Shiatsu massage, and transcranial direct current stimulation (tDCS). Findings showed that aromatherapy and Benson relaxation technique were effective in reducing anxiety and improving sleep quality, music therapy reduced anxiety during and after wound care, Swedish and Shiatsu massage increased relaxation, while tDCS significantly reduced pain and anxiety. This study recommends the integration of these techniques into nursing practice to improve the quality of care and patient satisfaction. Further studies are needed to confirm these findings and explore the mechanisms of action of each intervention in more depth.